EFFICACY STUDY OF PANCHARISHTA CHURNA IN DOOSHIVISHA WITH REFERENCE TO CONTACT DERMATITIS - Shinde, PriyaPopatrao; Joglekar, V.P. (International Journal of Research -GRANTHAALAYAH, 2017)
The amazing journey of Ayurveda from its divine origin to the present day has left us wondering about enormous potential this science possesses. Its successful existence since time immemorial itself proves its scientific approach attributed to its unique principles that have remained unchanged till date. The Ayurveda is categorized into eight divisions, which collectively called Ashtang Ayurveda. Agadtantra is one among those branches. This dissertation is an attempt to study the efficacy of “Pancharishtachurna” in Dooshivish with special reference to contact dermatitis. The main purpose of this work is to help the person who is suffering from Contact dermatitis and wants to cure from the disease. A Controlled Open prospective trial was carried out on 60 patients of ‘Contact dermatitis’, who were attended OPD & having history of Dooshivish poisoning. 30 patients were treated by Pancharishtachurna in study group and 30 patients were treated by Pancharishtachurna&Raktamokshana in control group at S.T.R.H.Pune.